2012
DOI: 10.2528/pier12072008
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Emc Performance of a Graded-Impedance, Microwave, Rice-Husk Absorber

Abstract: Abstract-Biomass used for energy, whether it is extracted from forest residues or agricultural waste, contributes in many areas, such as power production, the construction industry, and also as a major source of different organic and inorganic compounds in the petrochemical industry. In recent years, research has identified a very remarkable use of agricultural waste, especially rice husks, as a microwave absorber in a pyramidal shape. However, absorbers built in this shape are fragile and require a very high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…The conductivity of body tissue increases with frequency and consequence to high absorption loss [42,43]. Likewise some of the tissues (fat, skin, muscle, blood, intestine) show high dissimilar dielectric property with each other that result high impedance mismatch and high reflection loss [44,46,47] at the interface of these layer.…”
Section: Human Body Modelmentioning
confidence: 99%
“…The conductivity of body tissue increases with frequency and consequence to high absorption loss [42,43]. Likewise some of the tissues (fat, skin, muscle, blood, intestine) show high dissimilar dielectric property with each other that result high impedance mismatch and high reflection loss [44,46,47] at the interface of these layer.…”
Section: Human Body Modelmentioning
confidence: 99%
“…Such environmental pollution would be reduced if the rice husks were used in other applications rather than burned. Recently, several research projects involving rice husks have shown that the properties of rice husks make this waste material potentially useful as a microwave absorber and for other applications [2][3][4][5][6]. This is because 35-37% of the rice husks is carbon, which has the ability to attenuate/absorb microwave radiation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, in dealing with practical enclosures having openings along their sides, the amount of EM field leaking into (or exiting from) the enclosure can be greatly increased in the proximity of such resonant frequencies [3,5]. Therefore, it is a common practice to line internal surfaces of cabinets with properly designed absorbers in order to damp resonances [11][12][13].…”
Section: Introductionmentioning
confidence: 99%